Fighting inequalities in times of pandemic: The role of politicized identities and interdependent self‐construal in coping with economic threat. (13th June 2022) - del Fresno‐Díaz, Ángel; Estevan‐Reina, Lucía; Sánchez‐Rodríguez, Ángel; Willis, Guillermo B.; de Lemus, Soledad
Abstract: During the COVID‐19 pandemic, institutions encouraged social isolation and non‐interaction with other people to prevent contagion. Still, the response to an impending economic crisis must be through the collective organization. In this set of pre‐registered studies, we analyse two possible mechanisms of coping with collective economic threats: shared social identity and interdependent self‐construction. We conducted three correlational studies during the pandemic in May–October 2020 (Study 1, N  = 363; Study 2, N  = 250; Study 3, N  = 416). Results show that shared identity at two levels of politicization (i.e., working‐class and 99% identities) and interdependent self‐construal mediated the relationship between collective economic threat, intolerance towards economic inequality and collective actions to reduce it. The results highlight that the collective economic threat can reinforce the sense of community—either through the activation of a politicized collective identity, such as the working class or the 99% or through the activation of an interdependent self—which in turn can trigger greater involvement in the fight against economic inequality. Please refer to the Supplementary Material section to find this article's Community and Social Impact Statement .